2006
DOI: 10.1007/pl00022253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rabeprazole or famotidine during cardiac surgery on perioperative gastric and esophageal pH readings

Abstract: The FAM group and RPZ group revealed a sufficient effect of gastric acid suppression. It was indicated that FAM had an insufficient effect of gastric acid suppression for HP-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Munakatar et al [23] did not find a relation between gastric acid secretion and stress ulceration. Some studies demonstrated suppression of acid secretion and benefit in patients given routine stress ulcer prophylaxis [24,25]. These results suggest that acute acid secretion may contribute to stress peptic ulcer.…”
Section:  Physiological Stressmentioning
confidence: 89%
“…Munakatar et al [23] did not find a relation between gastric acid secretion and stress ulceration. Some studies demonstrated suppression of acid secretion and benefit in patients given routine stress ulcer prophylaxis [24,25]. These results suggest that acute acid secretion may contribute to stress peptic ulcer.…”
Section:  Physiological Stressmentioning
confidence: 89%